DINAMIKA KOMUNIKASI DALAM ERA DIGITAL : TANTANGAN DAN PELUANG - Nurul Fadhilah (Journal of Dialogos, 2024)
This article discusses the dynamics of communication in the context of the digital era, identifying challenges that arise along with technological developments, as well as opportunities that can be utilized to enrich communication. This research uses a qualitative approach.  The results of this study explain that the challenges of communication in the digital era are information overload, filter bubble, crisis of trust, data insecurity. Opportunities in the dynamics of digital communication are global reach, public participation, communication innovation and digital literacy development.